If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -24n + 24 + 2n = 0 Reorder the terms: 24 + -24n + 2n = 0 Combine like terms: -24n + 2n = -22n 24 + -22n = 0 Solving 24 + -22n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -22n = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -22n = 0 + -24 -22n = 0 + -24 Combine like terms: 0 + -24 = -24 -22n = -24 Divide each side by '-22'. n = 1.090909091 Simplifying n = 1.090909091
| -6a+4=a+9-2a | | 7x-4(x-6)=2(x-8) | | 3j-2j+8=2j+1 | | 4-10x/25=185 | | X-32+4=12 | | 4x+8-6= | | 7-1/4(8p-8)-5p | | n/9+7=10 | | -2x-8=-12 | | 0.5(2-4w)=2w-9 | | 3X-y+8=0 | | 7-7x=-6 | | 0.5(2-4a)=2w-9 | | 18=-6x+x-2 | | (x-5)/10+(1+2x)/5=(3-x)/4 | | 40*2=110/1,5 | | 2m+4m-3=9 | | -x/12=-1 | | x+6=34*1.5 | | 5x^2+25x+20= | | -68=x+7x+4 | | 3x-2=34*2 | | 11(x-2)=6x+13 | | 3(x+1)+37=-2x | | x+x+6+3x=86 | | 9x+7=5x+11 | | 3x-2=13x-61 | | x-76/7=4/5 | | n/6+6=8 | | 81y^2=25 | | -9(-8)-8= | | 3(X-5)+4=(x+4)-2 |